Methodological Conditions for the Design of the Entrance Groups of the Service Establisments Built-in Into the Apartment Houses - Абизов, В. А.; Кулик, А. В. (Art and Design, 2019)
Determination of the basic methodological provisions for the formation of the design service enterprises' entrance groups built-in into the residential buildings. Consideration of design features of the entrance groups of built-in objects in accordance with the hierarchical levels of formation of their architectural environment. The research is based on a systematic approach that allows us to consider the architectural environment of entertaining institutions as hierarchically subordinate to the integrity. Also are used methods of historical, comparative and typological analysis, experimental design. The article comprehensively examines the various factors and conditions that influence on the organization of the architectural environment of the service enterprises' entrance groups located on the first floors of residential buildings. The main stages of designing and the corresponding hierarchical levels of formation of the design of the service objects' entrance groups, are revealed.  The proposed method of designing of service enterprises' entrance groups of built-in into the apartment houses is proposed. The peculiarities of the design of entrance groups in accordance with the revealed hierarchical levels of formation and development of their architectural environment are presented. The given methodological provisions regarding the formation of the design of service enterprises' entrance groups of built-in into the apartment houses will be useful for the current practice of designing, rehabilitating, modernizing and exploiting the built-in service objects and will contribute to solving the problem of aesthetic expressiveness of residential development.